Minimizing ammonia volatilization in waterlogged soils through mixing of urea with zeolite and sago waste water. - Omar, Latifah; Ahmed, Osumanu Haruna; Nik Ab. Majid, Nik Muhamad (Academic Journals, 2010)
Loss of ammonia through volatilization is one of the major mechanisms which lead to poor urea-N use efficiency. In line with this, a laboratory study was carried out to determine the effect of mixing urea with zeolite and sago waste water on ammonia volatilization, soil exchangeable ammonium and available nitrate contents compared with urea without additives under waterlogged condition. The soil used in the experiment was Bekenu series (Fine loamy, siliceous, isohyperthermic, red-yellow to yellow Tipik Tualemkuts). This study was compared with five different mixture treatments which are: soil alone (T0), urea without additives (T1), urea mixed with 175 mL sago waste water and 0.75 g zeolite (T2), urea mixed with 175 mL sago waste water and 1.0 g zeolite (T3), and urea mixed with 175 mL sago waste water (T4). The mixtures (T2, T3 and T4) significantly minimized ammonia volatilization by between 40 and 50% compared with urea without additives (T1). These treatments (T2, T3 and T4) also significantly improved retention of soil exchangeable ammonium by 40 to 50% compared with urea without additives (T1). Additionally, the treatments significantly increased soil available nitrate nitrogen compared to urea without additives. Ammonia volatilization from urea could be significantly minimized under waterlogged condition, if urea is amended with sago waste and zeolite. Urea-N efficiency could be increased in waterlogged soils as the approach adopted in this study ensures effective retention of soil exchangeable ammonium and timely availability of soil nitrate nitrogen for plant use.